Studi Kitab Tafsīr Al-Qur’ān Al-Aẓīm Karya Ibnu Kaṡīr - Abd Haris Nasution; Muhammad Mansur (Jurnal Ushuluddin Adab dan Dakwah, 2018)
Ibn Katsir is a prominent scholar of the 8th century of Hijriyyah, who is expert in the field of tafsir, hadith, dates, and fiqh. This scholarly scholar is much influenced by the thought of his teacher, Ibn Taymiyyah. Included in the principles of the interpretation of the Qur'an as set out in the introduction of the book of his tafsir. Tafsir Ibnu Katsir is an interpretation of the pattern and orientation of bi al-ma'tsur or bi ar-riwayah, by tahlili (analytical) method. The book generally occupies the second position after Tafsir al-Thabari. However, in terms of his criticism or historical selection, simplicity, as well as his native language, Tafsir Ibnu Katsir is better than al-Thabari's tafsir. Ibn Katsir is very dominant in using history / hadith. This is influenced by his author's expertise in the field of hadith and the history of his tradition. He was also very critical of Israiliyat's history, though there were small numbers who escaped his criticism. Various attitudes and views of Ibn Katsir when interpreting verses (nuances) muhkam-mutasyabih, tasybih, naskh, history, fiqh, and so forth, show him an interpretative, hadith, history, and fiqh, which is critical and selective. His thinking is more in line with the salaf scholars who prioritize revelation (al-Qur'an and hadith), and put reasoning thereafter.